2010
DOI: 10.1093/neuonc/noq054
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic/ultrasound focusing system enhances nanoparticle drug delivery for glioma treatment

Abstract: Malignant glioma is a common and severe primary brain tumor with a high recurrence rate and an extremely high mortality rate within 2 years of diagnosis, even when surgical, radiological, and chemotherapeutic interventions are applied. Intravenously administered drugs have limited use because of their adverse systemic effects and poor blood-brain barrier penetration. Here, we combine 2 methods to increase drug delivery to brain tumors. Focused ultrasound transiently permeabilizes the blood-brain barrier, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 34 publications
1
68
0
1
Order By: Relevance
“…Also, because SPIO nanoparticles respond to external magnetic forces, magnetic targeting can actively enhance their deposition at the target site, increasing the therapeutic dose delivered beyond that obtainable by passive diffusion into BBB-disrupted regions. It has been demonstrated that conjugating SPIO with a chemotherapeutic agent can treat brain tumors in rodents (34,35). SPIO proved effective both as an image indicator (to identify distribution of chemotherapeutic drugs after BBB disruption) and as a means of increasing treatment efficacy when used in conjunction with magnetic targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because SPIO nanoparticles respond to external magnetic forces, magnetic targeting can actively enhance their deposition at the target site, increasing the therapeutic dose delivered beyond that obtainable by passive diffusion into BBB-disrupted regions. It has been demonstrated that conjugating SPIO with a chemotherapeutic agent can treat brain tumors in rodents (34,35). SPIO proved effective both as an image indicator (to identify distribution of chemotherapeutic drugs after BBB disruption) and as a means of increasing treatment efficacy when used in conjunction with magnetic targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were found when using BCNU. 10 , significance not reported). Results from low-and high-dose MNPs demonstrated that this effect was dose dependent.…”
Section: Nanoparticle Conjugation and Mrgfusmentioning
confidence: 92%
“…6). 8 However, for groups receiving high-dose therapeutic MNPs (equivalent to 5 mg/kg of BCNU), tumor volumes were suppressed in the 1st week, both with and without applying FUS/magnetic targeting (-52% and -97%, respectively). The medium dose (equivalent to 1 mg/kg BCNU) appeared to represent the critical dose for suppression of tumor growth when FUS/magnetic targeting is applied (-79%), but tumors progressed in the sham group (296%).…”
Section: Dose-dependent Therapeutic Mnps: In Vivo Considerationsmentioning
confidence: 98%
“…2A) for treatment of gliomas has also been investigated to determine the optimal enhancement conditions. 8 Normal/ glioma rats were subjected to various treatments to compare their efficacy in delivering localized concentrations of nanoparticles to a specific region of the brain. Quantitative inductively coupled plasma optical emission spectrometry analysis of Fe content revealed that FUS alone or magnetic targeting alone only increased therapeutic MNP concentrations by 2-fold relative to the untreated brain.…”
Section: Dose-dependent Therapeutic Mnps: In Vivo Considerationsmentioning
confidence: 99%
See 1 more Smart Citation